2007
DOI: 10.1021/jp066812k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Preparation Route of Bimetallic Pt−Au Nanoparticle Electrocatalysts for the Oxygen Reduction Reaction

Abstract: Pt and Au are not miscible within a whole range of concentrations. To obtain PtAu alloys, severe thermal treatments are required that to provide aggregation phenomena. However, it is possible to synthesize bimetallic PtAu nanoparticles provided the proper synthesis route is employed. When they are prepared from water-in-oil microemulsions or with the impregnation technique, it is possible to obtain nanosized bimetallic PtAu particles. In contrast, other colloidal routes have been seen to be adequate for the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
137
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 50 publications
7
137
0
Order By: Relevance
“…Bimetallic Pt-Au clusters have a wide range of catalytic applications, including oxygen reduction in fuel cells (Hernández-Fernández et al 2007), methanol and formic acid oxidations (Zhang et al 2008;Peng & Yang 2009) and selective oxidations (Bond et al 2006). In the bulk Pt/Au system, there is a miscibility gap at low temperature where Pt and Au are immiscible and Au prefers to segregate to the surface because of its lower surface energy (Okamoto & Massalski 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic Pt-Au clusters have a wide range of catalytic applications, including oxygen reduction in fuel cells (Hernández-Fernández et al 2007), methanol and formic acid oxidations (Zhang et al 2008;Peng & Yang 2009) and selective oxidations (Bond et al 2006). In the bulk Pt/Au system, there is a miscibility gap at low temperature where Pt and Au are immiscible and Au prefers to segregate to the surface because of its lower surface energy (Okamoto & Massalski 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Cationic Au-Pt clusters have shown unique reactivity for C-N coupling of methane and ammonia. 11,12 Recently it has been reported that carbon-supported Au-Pt bimetallic NPs display performances better or similar to those of pure platinum supported on carbon for oxygen reduction, 13,14 provided alloyed and not phasesegregated Au-Pt NPs are used. It has been also shown that platinum could be partially substituted by gold for application in methanol oxidation: higher resistance to poisoning was observed in acidic media with Au-Pt bimetallic NPs, while in alkaline environment a significant overall improvement in performance was reported.…”
Section: Introductionmentioning
confidence: 99%
“…16 The microemulsion and the impregnation routes proved effective, in contrast to the colloidal procedure. 13 Organometallic or coordination complex precursors could also be used with the drawback of pre-imposed Pt-to-Au atomic stoichiometry. 4,17 In this context, it is assumed that radiolytic reduction might provide a convenient route to synthesize alloyed Au-Pt NPs exhibiting desired physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…No doubt, all these factors will operate in the course of reactions making the electrocatalysis and reaction mechanism highly complex. From synthesis point of view, the main methods for preparing multi-metallic catalysts, that are currently used in the field of electrocatalysis, are e.g., colloidal, [19][20][21][22][23] micro-emulsion [24][25][26][27][28] and the carbonyl chemical route. [29][30][31][32][33][34][35][36] The problem with particles of nanometric size is the fact that they are usually not thermodynamically stable and might change over time or during reaction conditions, and corrosioninduced dissolution of alloying components leads to surface roughening.…”
Section: Introductionmentioning
confidence: 99%